The Analysis of Einar’s Gender Identity in “The Danish Girl” by David Ebershoff - Gunawan Gunawan (International Journal Labs, 2021)
This study aims to discover LGBT has become the most potential threat to the existence of sexual identity. In some religious countries, LGBT which stands for Lesbian, Gay, Bisexual and Transgender will give complicated conflicts. It raises the pros and cons in the society. This study investigates LBGT as the unfamiliar issues in societies as reflected in The Danish Girl by David Ebershoff. This issue sometimes becomes ‘scourge’ because it against the principle of certain religion. LGBT is considered to violate the nature to which has been given by God. This issue is a ‘scourge’ in some societies groups. Meanwhile, it is often discussed by certain institutions supporting LGBT. This study is a qualitative research which applies Harry Benjamin’s theory of transsexual related to gender studies. The results reveal that 1) Einar Wegener is described as a man who has feminine tendency, submissive, inferior and emotional, 2) there are internal conflicts such as Einar’s having less confident in wearing man’s clothes, being sexually attracted to the same gender and struggling for identity determination, 3) Having the presence of finding identity, Einar has solution for his identity how to be a real woman by genital surgery.